Pelatihan dan Pendampingan Desain RPP Berbasis Dinul Islam dan Penulisan Penelitian Tindakan Kelas bagi Guru Matematika Sekolah Menengah Kejuruan Kota Lhokseumawe - Yusnaini; Setiawan (Medan Resource Center, 2022)
Activities carried out in community service for mathematics teachers at Vocational High Schools (SMK) in Lhokseumawe City are activities to write Classroom Action Research (PTK) and design Learning Implementation Plans (RPP) based on Islamic Dinul. The purpose of this activity is that math teachers at Lhokseumawe City Vocational Schools are able to make PTK and design lesson plans based on Dinul Islam on an ongoing basis in order to improve teacher careers. The form of this activity is by carrying out training and mentoring for 4 days from 26 to 29 April 2021 with a total time of 32 JP with an allocation of 2 days for training and assistance in writing PTK and 2 days for designing lesson plans based on Dinul Islam. Then proceed with assistance in the form of guidance in writing PTK and lesson plans based on Dinul Islam from May to June 2021. The work system carried out by the teacher is group in nature, each group consists of 3 people and works together in determining the PTK title and continuing with writing PTK. Meanwhile, the work system in designing RPP based on Dinul Islam is individual. The results obtained resulted in 10 PTK titles with writing that were still continuous, while Dinul Islam based lesson plans had been printed and collected as many as 26 lesson plans from 30 participants.